Periostin promotes the generation of fibrous membranes in proliferative vitreoretinopathy. Issue 1 (10th September 2013) - Ishikawa, Keijiro; Yoshida, Shigeo; Nakao, Shintaro; Nakama, Takahito; Kita, Takeshi; Asato, Ryo; Sassa, Yukio; Arita, Ryoichi; Miyazaki, Masanori; Enaida, Hiroshi; Oshima, Yuji; Murakami, Noboru; et al.
Abstract : Proliferative vitreoretinopathy (PVR) is a severe, vision‐threatening disorder characterized by the fibrous membrane formation that leads to trac‐tional retinal detachment. There has been no effective therapeutic approach other than vitreoretinal surgery. In this study, DNA microarray analysis of the fibrous membranes revealed significant up‐regulation of periostin. We also found increased periostin expression in the vitreous and retinal pigment epithelial (RPE) cells from fibrous membranes of PVR patients. In vitro, periostin increased proliferation, adhesion, migration, and collagen production in RPE cells through integrin αVmediated FAK and AKT phosphorylation. Periostin blockade suppressed migration and adhesion induced by TGFβ2 and PVR vitreous. In vivo, periostin inhibition had the inhibitory effect on progression of experimental PVR in rabbit eyes without affecting the viability of retinal cells. These results identified periostin as a pivotal molecule for fibrous membrane formation as well as a promising therapeutic target for PVR.—Ishikawa, K., Yoshida, S., Nakao, S., Nakama, T., Kita, T., Asato, R., Sassa, Y., Arita, R., Miyazaki, M., Enaida, H., Oshima, Y., Murakami, N., Niiro, H., Ono, J., Matsuda, A., Goto, Y., Akashi, K., Izuhara, K., Kudo, A., Kono, T., Hafezi‐Moghadam, A., Ishibashi, T. Periostin promotes the generation of fibrous membranes in proliferative vitreoretinopathy. FASEB J. 28, 131–142 (2014). www.fasebj.org